GC-MS Analysis and Antiproliferative Effect of Ethanolic Extract of Apium graveolens L. seeds on MCF-7 Human Breast Cancer Cell Lines - Iyer, Deepa; Siddiqui, Nafeesa; Patil, Umesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: The aim of this study was to identify main phytocompounds and to evaluate the antiproliferative effect of the ethanolic extract of Apium graveolens seeds. Materials and Methods: in vitro antiproliferative study of A. graveolens ethanolic extract was investigated against MCF-7 cells breast cancer cell lines using the MTT colorimetric assay. Further, the main bioactive components were elucidated by Gas Chromatography–Mass Spectrometry (GC–MS). Commercial mass spectral library was used for the depiction of individual phytocomponents. Results: Terpenes were the main compounds found in the ethanolic extract of seeds of A. graveolens. In antiproliferative assay, the ethanolic extract in analysis showed significant activity in the proposed conditions. About six components were identified through GC-MS. This study showed the presence of different phytocomponents like Oleanane-3, 16-diol, 13, 28-epoxy-, diacetate, (3.beta., 16.alpha.) [Triterpenes]; Bacchotricuneatin C [Diterpene Lactone]; Cyclopropa[5,6]cholestane, 3-ethoxy-3',6-dihydro-, (3.alpha.,5.alpha.,6.beta.) [Phytosterol]; Fumaric acid, decyl 3-pentyl ester; Anthra[2,3-d]-1,3-dioxole-5,10-dione, 3a,4,11,11a-tetrahydro-9-hydroxy-7-methoxy-2,2,3a-trimethyl-, cis- [Glycoside]; Olean-12-en-28-oic acid, 3.beta.-hydroxy-21-oxo-, methyl ester [Triterpenes]. Conclusion: In-vitro cytotoxic activity of the ethanolic extract of the plant seeds has been evaluated and showed significant anti-proliferative effect against MCF-7 breast cancer cell lines. The study represents the first report of these compounds from Apium graveolens seeds ethanolic extract.
Keywords: Apium graveolens; GC-MS; Structural Elucidation; Phytocomponents; MCF-7; Antiproliferative